# =VAR(2X-Y)

## Simple and best practice solution for =VAR(2X-Y) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for =VAR(2X-Y) equation:

Simplifying
0 = VAR(2X + -1Y)
0 = (2X * ARV + -1Y * ARV)
0 = (2ARVX + -1ARVY)
Solving
0 = 2ARVX + -1ARVY
Solving for variable 'A'.
Move all terms containing A to the left, all other terms to the right.
Add '-2ARVX' to each side of the equation.
0 + -2ARVX = 2ARVX + -2ARVX + -1ARVY
Remove the zero:
-2ARVX = 2ARVX + -2ARVX + -1ARVY
Combine like terms: 2ARVX + -2ARVX = 0
-2ARVX = 0 + -1ARVY
-2ARVX = -1ARVY
Add 'ARVY' to each side of the equation.
-2ARVX + ARVY = -1ARVY + ARVY
Combine like terms: -1ARVY + ARVY = 0
-2ARVX + ARVY = 0
Factor out the Greatest Common Factor (GCF), 'ARV'.
ARV(-2X + Y) = 0
Subproblem 1Set the factor 'ARV' equal to zero and attempt to solve:
Simplifying
ARV = 0
Solving
ARV = 0
Move all terms containing A to the left, all other terms to the right.
Simplifying
ARV = 0
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
Subproblem 2Set the factor '(-2X + Y)' equal to zero and attempt to solve:
Simplifying
-2X + Y = 0
Solving
-2X + Y = 0
Move all terms containing A to the left, all other terms to the right.
Add '2X' to each side of the equation.
-2X + 2X + Y = 0 + 2X
Combine like terms: -2X + 2X = 0
0 + Y = 0 + 2X
Y = 0 + 2X
Remove the zero:
Y = 2X
Add '-1Y' to each side of the equation.
Y + -1Y = 2X + -1Y
Combine like terms: Y + -1Y = 0
0 = 2X + -1Y
Simplifying
0 = 2X + -1Y
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
The solution to this equation could not be determined.`